Applications of geospatial analyses in health research among homeless people: A systematic scoping review of available evidence. Issue 3 (September 2022) - Ahasan, Rakibul; Alam, Md Shaharier; Chakraborty, Torit; Ali, S M Asger; Alam, Tunazzina Binte; Islam, Tania; Hossain, Md Mahbub
Highlights: Reviewed literature from homeless population-public health issue-geospatial analysis nexus. Geographic disparity found in the existing works, no studies from the global south. All the studies found was from the developed countries and more than two-third study locations are from USA and Canada. Limited GIS use in examining public health concerns among homeless population. Developing countries could benefit by integrating open-source GIS techniques to leverage their limited resources. Abstract: Background: Unequal housing access resulted in more than 150 million homeless people worldwide, with millions more expected to be added every year due to the ongoing climate-related crises. Homeless population has a counterproductive effect on the social, psychological integration efforts by the community and exposure to other severe health-related issues. Geographic Information Systems (GIS) have long been applied in urban planning and policy, housing and homelessness, and health-related research. Methods: We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to systematically review 24 articles collected from multiple databases (n = 10) that focused on health-related issues among homeless people and used geospatial analysis techniques in their research. Results: Our findings indicated a geographic clustering of case study locations– 26 out of the 31 case study sites are from the USA and Canada. Studies used spatial analysis techniques to identify hotspots, clusters and patterns of patient location and population distribution. Studies also reported relationships among the location of homeless shelters and substance use, discarded needles, different infectious and non-infectious disease clusters. Conclusion: Most studies were restricted in analyzing and visualizing the patterns and disease clusters; however, geospatial analyses techniques are useful and offer diverse techniques for a more sophisticated understanding of the spatial characteristics of the health issues among homeless people. Better integration of GIS in health research among the homeless would help formulate sensible policies to counter health inequities among this vulnerable population group.